Background of choice forms of integration of agricultural enterprises during organization of reclamation service - Мандзюк, О. М. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
The article considers the recommendation for particular choice of forms of integration of agricultural enterprises in the process of organization reclamation services. The main form of enterprises' integration on reclaimed land such as association of earth water users, agricultural service cooperatives, corporate structures, joint stock companies with state share ownership are proposed. The main parameters of the integrated structures efficiency, including the localization of agricultural land, the costs of reclamation services, transaction costs associated with finding contractors, implementation of standards, costs and expenses, compatibility purposes, obligations to contractors are suggested. A list of factors that determine the choice integration forms are indentified.